2016
DOI: 10.18785/jetde.0901.01
|View full text |Cite
|
Sign up to set email alerts
|

How Fast is Fast Enough? Education Students’ Perceptions of Email Response Time in Online Courses

Abstract: An unintended consequence of the ubiquitous use of email for online course

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…E-mail is regarded as a preferred mode of communication in this study. This relates to a study by Chang et al (2016), where e-mail was also found to be the preferred mode of correspondence. A similar study regarding the use of mobile technology to enhance library services in Ghana confirmed that students often use WhatsApp to engage with library services (Akeriwa et al , 2015).…”
Section: Discussion Of the Findingssupporting
confidence: 54%
See 1 more Smart Citation
“…E-mail is regarded as a preferred mode of communication in this study. This relates to a study by Chang et al (2016), where e-mail was also found to be the preferred mode of correspondence. A similar study regarding the use of mobile technology to enhance library services in Ghana confirmed that students often use WhatsApp to engage with library services (Akeriwa et al , 2015).…”
Section: Discussion Of the Findingssupporting
confidence: 54%
“…Communication and interaction in the e-learning environment are very important to build an online community (Chang et al , 2016). To deliver a high-quality service, response time is very important.…”
Section: Resultsmentioning
confidence: 99%
“…There is no response time delay in synchronous communication because it happens in real time, unlike MIM quasi-synchronous communication where there is often some short delay. MIM is different from asynchronous communication (e.g., emails, forum discussions) because most MIM messages are answered promptly (Andujar, 2019 ) within 60 s (as in the case of WhatsApp) (Rosenfeld et al, 2018 ), whereas the average response time of asynchronous communication is markedly longer—24 h for email (Chang et al, 2016 ) and 24 to 48 h for online discussion forums (Jeong & Frazier, 2008 ). Figure 1 illustrates the differences between asynchronous, synchronous, and quasi-synchronous communication with examples.…”
Section: Introductionmentioning
confidence: 99%